KEWAJIBAN PERUSAHAAAN DALAM PELAKSANAAN TANGGUNG JAWAB SOSIAL (CORPORATE SOCIAL RESPONSIBILITY) - Muhammad Taufiqurrahman; Hendryanto Sitepu (Pascasarjana UDA, 2020)
Companies in carrying out social responsibility (Corporate Social Responsibility) do not only pursue profit but have an obligation to develop ethics, habits that apply in the community and the quality of the community around the company. This type of research is normative juridical research. Normative juridical research is research focused on studying the application of positive legal norms or norms while the nature of the research is analytical descriptive. The research findings show the benefits of corporate social responsibility (CSR) as a form of business field commitment to carry out business activities based on ethical values ​​with the aim of providing balanced attention and contribution both to the internal parties of the company and to the community and other stakeholders in order to realize a sustainable and sustainable development process, concern for the environment, legal arrangements for corporate social responsibility, Law on environmental protection and management, Law on Investment, Law on Oil and Gas, Law on Mineral Mining, Law on PT. It is expected that the stakeholders of CSR interests to run by referring to regulations to realize environmental stewardship.